Atividade da adenosina deaminase em diferentes períodos após a hipóxia-isquemia neonatal em córtex de ratos - Pimentel, Victor Camera (2009)
Neonatal hypoxic-ischemic injury (HI) is the direct complication to severe choking and may cause brain damage. HI may be found in different stages and clinical manifestations contributing to neonatal morbidity and mortality. The neuropathology of neonatal HI insult is multi-factorial and complex. Hypoxic-ischemic brain damage begins during the insult and extends during the recovery period after reperfusion, thus, it is an evolutionary process. Adenosine deaminase (ADA) is an aminohidrolase actively involved in the metabolism of purines catalyzing irreversibly adenosine and 2'desoxiadenosine into inosine and 2'desoxinosine, respectively. The objectives of this study were to evaluate the activity of ADA in the cortex of rats subjected to neonatal HI at different post-insult time points. Effects of thiobarbituric acid reactive species (TBARS) levels were also assessed in cortex. The histological analysis was evaluated using hematoxylin eosin (HE) and glial fibrillary acidic protein (GFAP) in the cortex of these animals. The ADA activity was significantly increased 8 days after the insult in the left hemisphere in the cortex. In this period, TBARS levels were significantly increased in the cortex of these animals. HE revealed the presence of ischemic area in the cerebral cortex 8 days after HI. A moderate lymphocytic infiltration was also evidenced in the cortex during this period. A proliferation and an increase in the expression of GFAP in the periphery of the ischemic area was observed, resulting in astrocytosis in the cortex of these animals. In conclusion, an activation of the immune system was observed due to the inflammatory process caused by the HI insult that may be correlated with astrocytosis and lymphocytic infiltration observed in the cerebral cortex of animals that suffered insult 8 days after neonatal HI.